Corpo potência e política - Espinosa e os direitos das mulheres - Maria Luísa Ribeiro Ferreira (Araucaria, 2018)
This paper intends to present the different meanings of “body” in Spinoza’s philosophy, attending to its physical, psychic, metaphysical and political meanings. It also presents the double condition of bodies - either while existing in duration or when directly thought by God. The concept of “conatus” and its importance in all bodies, is a pretext to visit the recent work of Antonio Damásio, The Strange Order of Things, and to compare the individual power present in all individuals with the political power in human societies. In this prospect we comment how Spinoza considers the feminine condition, trying to understand why he excludes women from a democratic government. About this issue we critically analyse the perspective of some feminist philosophers (Geneviève Lloyd, Moira Gaytens, Beth Lord e Margaret- Gullan Wuhr). The paper ends with a question «Can women participate in “amor intellectualis Dei”?», stating that in Ethics V we find an affirmative answer to this question.